Problems and Prospects of Local Judicial Committee in Nepal - Timilsina, Krishna Prasad (Journal of Political Science, 2020)
Decentralization and local governance is the base of grassroot democracy, giving strong foundation of democracy at nation. Local governments are the closest unit of people. Constitution of Nepal acknowledges that executive legislative and judicial bodies may be formed at the local level. Constitution provides to consolidate socialism-oriented federal democratic republic governance right from the local level as per the principle of the rule of law and sustainable development through proportionally inclusive and just distribution of the fruits of democracy, and to make necessary provisions in relation to the operation of the local government to institutionalize the legislative, executive and judicial practice at the local level by consolidating local government through development of local leadership. This article aims at examining current provision of judicial power in local government of Nepal, its service delivery status, analyzing challenges of justice delivery. To draw the conclusion in this study descriptive analytical and content analysis method has been used and information has been taken from secondary method.